2020
DOI: 10.1002/jum.15599
|View full text |Cite
|
Sign up to set email alerts
|

Role of Doppler Ultrasound Analysis of Blood Flow Through the Ophthalmic and Intracranial Arteries in Predicting Neurologic Symptoms During Carotid Endarterectomy

Abstract: Objectives Carotid endarterectomy (CEA) is frequently performed under locoregional anesthesia. The intraoperative clamping of the internal carotid artery (ICA) leads to cerebral hypoperfusion, which may in some patients result in the development of neurologic symptoms (NS). The objective of our study was to investigate whether there is an association between the preoperative ultrasound (US) Doppler flow in the ophthalmic artery (OA) and intracranial artery and the occurrence of these intraoperative NS. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hence, this reverse flow can serve as an important clinical sign of impaired cerebral hemodynamics and vasomotor reactivity [ 3 , 7 ]. In addition, stroke patients with ROAF have been reported to have worse outcomes than patients without ROAF [ 4 , 8 ]. When one segment of neurological tissue is in a compromised hemodynamic state, it redirects blood flow from ocular tissue, resulting in ROAF and a decrease in OPP [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this reverse flow can serve as an important clinical sign of impaired cerebral hemodynamics and vasomotor reactivity [ 3 , 7 ]. In addition, stroke patients with ROAF have been reported to have worse outcomes than patients without ROAF [ 4 , 8 ]. When one segment of neurological tissue is in a compromised hemodynamic state, it redirects blood flow from ocular tissue, resulting in ROAF and a decrease in OPP [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, significant differences were found in changes in stenosis levels and plaque enhancement between patients with/without stroke recurrence, and the changes showed correlations between stenosis and plaque enhancement, as well as with subsequent recurrent stroke [ 16 ]. Previous studies have also reported that reversal of ophthalmic artery before carotid stenting is associated with poorer prognosis [ 3 , 4 , 7 ]. However, high risk for recurrent ischemic stroke in patients with carotid stenosis post stenting phase is yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of reversed ophthalmic artery flow is higher in patients with severe carotid stenosis and acute stroke [ 3 6 ]. Stroke patients with reversed ophthalmic artery flow are reported to have worse outcomes than those without [ 3 , 4 , 7 ], while patients with MCA stenosis and reversed ophthalmic artery flow have higher risk of stroke recurrence [ 3 ]. In posterior circulation stroke, the prevalence of basilar artery/vertebral artery (BA/VA) stenosis > 50% is 20–30% in patients with ischemic stroke or transient ischemic attack, and BA/VA stenosis is also associated with recurrent stroke and mortality in these patients [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%